2014
DOI: 10.5114/pg.2014.42498
|View full text |Cite
|
Sign up to set email alerts
|

The role of gastrointestinal hormones in the pathogenesis of obesity and type 2 diabetes

Abstract: Obesity, influencing the increase of incidence of type 2 diabetes, cardiovascular complications and cancer is a growing medical problem worldwide. The feelings of hunger and satiety are stimulated by the “gut-brain axis”, where a crucial role is played by gastrointestinal hormones: glucagon-like peptide 1, glucose-dependent insulinotropic polypeptide, pancreatic polypeptide, peptide YY, oxyntomodulin, cholecystokinin and ghrelin. These hormones affect not only the functioning of the digestive tract, but also m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 86 publications
1
29
0
3
Order By: Relevance
“…Moreover, this hormone promotes gallbladder motility and the release of bile into the duodenum [6]. Pancreatic polypeptide controls exocrine function of the pancreas [7] in response to hunger and satiety signaling from the gut-brain axis [8], and reduces gastric emptying [8]. Ghrelin contributes to gastrointestinal motility, regulation of appetite, response to hunger and starvation [3,[9][10][11][12][13][14][15][16][17][18][19], and inhibits nausea [18].…”
mentioning
confidence: 99%
“…Moreover, this hormone promotes gallbladder motility and the release of bile into the duodenum [6]. Pancreatic polypeptide controls exocrine function of the pancreas [7] in response to hunger and satiety signaling from the gut-brain axis [8], and reduces gastric emptying [8]. Ghrelin contributes to gastrointestinal motility, regulation of appetite, response to hunger and starvation [3,[9][10][11][12][13][14][15][16][17][18][19], and inhibits nausea [18].…”
mentioning
confidence: 99%
“…In addition, the gastrointestinal tract has the largest numbers of endocrine and immune cells in the body. Therefore, except for the three gut hormones we investigated, GBP may result in changes of other important hormones or inflammatory cytokines that affect diabetes such as ghrelin (19) and IL-1b (20). Some studies reported positive results about ghrelin (21) and IL-1b (22) in RYGB.…”
Section: Discussionmentioning
confidence: 86%
“…Ведущую роль в обеспечении гуморальной (гомеостатической, периферической) регуляции играют гормоны желудочно-кишечного тракта (ЖКТ) и жировой ткани (ЖТ) [4]. Известно более 20 гормонов, в различной степени вовлеченных в регуляцию ПП и обладающих орексигенными или анорексигенными эффектами [4,5]. Среди гормонов, обладающих орексигенным действием, ведущую роль играет грелин, а наиболее значимыми ано-рексигенными гормонами являются гормон ЖКТ глюкаго-ноподобный пептид-1 (ГПП-1) и гормон ЖТ лептин.…”
unclassified
“…Adamska E. и соавт. [5] отметили более выраженное уменьшение уровня грелина после еды у тучных людей. Однако в большинстве исследований отмечено недоста-точное снижение грелина плазмы после еды или его от-сутствие у пациентов с ожирением, инсулинорезистент-ностью (ИР) и сахарным диабетом 2 типа (СД2) [10,11], что может способствовать увеличенному потреблению пищи из-за отсутствия своевременного появления чув-ства насыщения и формированию патологического ПП.…”
unclassified